2009
DOI: 10.28945/1078
|View full text |Cite
|
Sign up to set email alerts
|

A Conceptual Model for Learning to Program in Introductory Programming Courses

Abstract: The purpose of this paper is to develop a conceptual model for learning to program in entry level programming courses. The intended model is aimed at providing a framework to simplify learning to program at beginner or entry level programming courses. Learning to program is considered to be a difficult task to many students and it has been attributed to the continuous decline in enrollment in technology programs lately. The conceptual model being worked on in this paper is developed along another model widely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Malik & Coldwell-Neilson [23] presented a model using ADRI to help novices overcome problems in choosing the right problem-solving strategies. Ali [24] introduced a model based on a modified version of the system development lifecycle (SDLC), where students solve tasks through the planning, coding, and output phases.…”
Section: Framework and Modelsmentioning
confidence: 99%
“…Malik & Coldwell-Neilson [23] presented a model using ADRI to help novices overcome problems in choosing the right problem-solving strategies. Ali [24] introduced a model based on a modified version of the system development lifecycle (SDLC), where students solve tasks through the planning, coding, and output phases.…”
Section: Framework and Modelsmentioning
confidence: 99%
“…Educators have indicated that, in educational computer games, the teaching content is presented vividly and interestingly, and hence attracts students to learn (Dickey 2011b;Garris et al 2002). Ali (2009) indicated that in an educational computer game learning contents are abstracted and presented graphically, allowing pupils to comprehend the concepts to be learned and the questions to be resolved more easily.…”
Section: Digital Game-based Learningmentioning
confidence: 99%